2017
DOI: 10.1021/acs.est.6b06277
|View full text |Cite
|
Sign up to set email alerts
|

Transformation and Sorption of Illicit Drug Biomarkers in Sewer Biofilms

Abstract: In-sewer transformation of drug biomarkers (excreted parent drugs and metabolites) can be influenced by the presence of biomass in suspended form as well as attached to sewer walls (biofilms). Biofilms are likely the most abundant and biologically active biomass fraction in sewers. In this study, 16 drug biomarkers were selected, including the parent forms and the major human metabolites of mephedrone, methadone, cocaine, heroin, codeine, and tetrahydrocannabinol (THC). Transformation and sorption of these sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
60
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(68 citation statements)
references
References 44 publications
7
60
0
Order By: Relevance
“…except for KET with closer distributions of at minor levels. This could be ′ explained by the stronger biological activities of biofilms in the pilot sewer pipes and the sewer reactors of Li et al 10 compared to biofilms in the reactors of McCall et al 14 and/or Ramin et al 16 Moreover, and/or appear to be generally equivalent…”
Section: Model Performance Evaluation I: the Different K-value Setsmentioning
confidence: 97%
See 3 more Smart Citations
“…except for KET with closer distributions of at minor levels. This could be ′ explained by the stronger biological activities of biofilms in the pilot sewer pipes and the sewer reactors of Li et al 10 compared to biofilms in the reactors of McCall et al 14 and/or Ramin et al 16 Moreover, and/or appear to be generally equivalent…”
Section: Model Performance Evaluation I: the Different K-value Setsmentioning
confidence: 97%
“…(h -1 ) represents the processes in the bulk liquid wastewater, mainly μ chemical hydrolysis assuming that the sorption to suspended solids or biofilm is limited for investigated biomarkers 5,14,16,33 and the biological activity of suspended solids is negligible compared to the sewer biofilms or sediments. [34][35][36] It is further postulated that remains the same under aerobic and anaerobic conditions, according to the findings of McCall et al 14 To calibrate the transformation model, experimental datasets obtained from the pilot rising main pipe (Day and 2) and the pilot gravity sewer (Day 4 and 5) pipe were used to estimate and , respectively, through a Bayesian procedure ′ ′ described in Li et al 10 The datasets of Day 3 (rising main) and Day 6 (gravity sewer)…”
Section: Calibration Of Drug Transformation Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Many laboratory experiments used bulk liquid wastewater in a container to represent the sewer conditions (Ostman et al 2014, Senta et al 2014, and other studies utilized sewer reactors that have biofilms (Gao et al 2017, O'Brien et al 2017, Ramin et al 2017, Thai et al 2014. These studies have found, for example, that the relatively fast degradation of cocaine and 6monoacetylmorphine compromised their usability as biomarkers in WBE.…”
Section: Introductionmentioning
confidence: 99%